DEVELOPMENT OF AN ONLINE STORE USING WORDPRESS AND WOOCOMMERCE FOR A TRADING COMPANY. CASE: PROFESSIONAL NURSING SERVICES - Presenda, Freddy Alberto Morcillo; Ferreira, Arturo Corona; de la Cruz, José Trinidad Acosta; Rodríguez , José Manuel Hernández; Reyna, Manuel Villanueva; Castañeda, Gustavo Adolfo Chapus (Seven Editora, 2025)
The adaptation to technology is becoming more and more common and important, since nowadays using the Internet is usually an indispensable tool to carry out any activity. Nowadays Internet is one of the most effective means to offer services to customers, therefore a web application will be developed using WordPress and WooCommerce to facilitate the hiring of professional services in nursing.DOI: https://doi.org/10.56238/sevened2025.021-023